Research competence formation of master’ of philology by means of discourse (Pedagogy of Higher and Secondary Education, 2015)
Nikitina A. V. Research competence formation of master’ of philology by means of discourse.The article includes scientific principles of research competence formation of masters of philology – the future teachers of Ukrainian language and literature, researchers of Ukrainianphilology. Also, the definition of “research competence of master of philology” is precised; the partial aspects of methodology of the pedagogical discourse are analyzed and their roles as the means of research competence formation of masters of philology are identified.
Keywords: research competence; masters of philology; pedagogical discourse; methodology of discourse